Un diagnóstico a la enseñanza de la ciencia política en Colombia (2007)
What is the scope of academic programs of the various universities that offer the training programs in Political Science at the undergraduate level (degree) in Colombian universities? How is the curriculum mesh developed in each one of these academic programs? To what are they responding? What debate drives the academic denomination of the programs offered by these universities? What is the training objective of each university, and do they instill this objective to the political scientists? These are the questions that at the time to formulate an academic program in Political Science guide in principle its creation. However, little or no political scientists speak about the matter, nobody reflects on the scope of Colombian political scientist’s training. Nevertheless, the concern and the need to make explicit the characteristics of political science in terms of vocational training are more than urgent. Thus, this paper aims to provide readers with a first approach and, if you will, an assessment of the process of Colombian political scientist’s training based on fourteen academic training programs currently in placeand properly registered with the National System of Higher Education Accreditation SNIES.